Risk Evaluation Of The Shipyard Supply Chain Process On Ship Repair With The House Of Risk Matrix Method - Hanif Ardhio Firmansyah; Intan Baroroh; Ali Azhar (Institut Teknologi Sepuluh Nopember, 2025)
One of the keys to the success of ship repair is the supply chain (SC) process of materials that arrive on time. However, delays in its implementation were still found due to poor SC risk management. The purpose of the study is to identify risk factors for SC delay, measure risk factors and evaluate risk factors. This study uses the HOR (House of Risk) method which identifies risk variables (risk events and risk agents) and designs mitigation actions. The results of the HOR phase 1 study show an assessment score in the form of Aggregate Risk potential (ARP) which has a high influence on KM repair. Lintas Damai 1 includes: Supplier's unpreparedness in fulfilling orders with a score of 225, the forwarder experienced a delay in scoring 116 and Needs rejuvenation of facilities and transportation with a score of 120 and KM. Shinpo19 includes the quality of materials from suppliers that are of poor quality with a score of 280, materials that are difficult to obtain in the area with a score of 138 and the layout of poorly organized storage warehouses with a score of 92. The results of HOR phase II include mitigation actions to handle risk agents in KM. Lintas Damai 1 includes finding trusted supplier partners, increasing networking with other suppliers, holding tenders with suppliers who are ready and conducting service and checks every month. Meanwhile, KM. Shinpo19 has mitigation actions to handle risk agents, namely replacing materials with the same specifications but still of quality, having supplier connections with quality standards, supervising suppliers so that they comply with quality standards and structuring materials based on their type.